Social work in hospice and palliative care in Europe: Findings from an EAPC survey. Issue 6 (December 2020) - Bitschnau, Karl W.; Firth, Pam; Wasner, Maria
Abstract: Objectives: Social work is considered to be a key player in Hospice and Palliative Care. To prove this claim, the Social Worker Task Force within the European Association for Palliative Care (EAPC) decided to carry out a survey. The aim of this survey was to generate basic data and thus to create a basis for further development of Palliative Care Social Work (PCSW) in Europe. Method: The online survey consisted of two parts: in Part 1, the 57 collective members of the EAPC were asked to fill in an online questionnaire containing questions about basic data. In Part 2, individual Palliative Care Social Workers (SWs) from all over Europe were asked to fill in another questionnaire with a focus on the basic conditions concerning their jobs as well, as on their tasks and roles. Results: Thirty-two collective members of the EAPC completed the online questionnaire. SWs can be found in all of the Palliative Care settings, but there are considerable differences between the countries concerning the prevalence of SWs. Only five countries (20%) reported specialized qualification training in PCSW and just around half of the responding SWs had such a specialized training. The responding SWs ( n = 360) were quite content with their working conditions. Tasks concerning patient and family and tasks concerning the interprofessional team were most prominent. There is a significant role overlap with other professions. Significance of results: The study reveals a very mixed picture of PCSW in Europe. This could be due to the high adaptability of social work, which is to be as flexible as possible to the needs of its clients. However, significant patterns, similarities, and differences emerge. The present study may, therefore, serve as a basis for further in-depth studies.